Comparison of Mammography, Sonography, Fine-Needle Aspiration Cytology, and Excision Biopsy for the Diagnosis of Breast Lesions (Perspectives In Medical Research, 2022)
Background and Objective: Problem of invasive tests in breast lesion diagnosis can be addressed by comparing non-invasive tests with final Histopathological diagnosis obtained after excision biopsy. Present study was carried out to study diagnostic utility of mammography, sonography, FNAC compared to excision biopsy for diagnosis of breast lesions